Cooperative Optimization Analysis of Variable-Speed and Fixed-Speed Pumped-Storage Units Under Large Disturbances in the Power System - Weidong Chen; Jianyuan Xu (Energies)
Aimed at the large disturbance of a power system caused by frequent new energy clusters going off-grid, we propose a cooperative optimization strategy of variable-speed and constant-speed pumped-storage units to address power oscillation due to significant power shortages following the clusters going off-grid. From a multi-time-scale perspective, we first investigate the fast power support control strategy of variable-speed pumped-storage (VSPS) units during new energy cluster off-grid scenarios. Using a consensus algorithm, the VSPS acts as the primary unit, while the constant-speed unit provides long-term power support. We present a rapid power control method for VSPS to prioritize frequency stability in mainland grids with high new energy penetration. This ensures stable power support for large-scale new energy clusters under large disturbances across multiple time scales. Simulation analysis on a high proportion of new energy power networks with new energy clusters confirms the effectiveness of our proposed method.